Evaluation of HBsAg, Anti-HCV, Anti-HIV Seroprevalence and Perinatal Outcomes in Pregnant Women. - Uçkan, Kazım; Çeleğen, İzzet; Uçkan, Taner (Viral Hepatitis Journal / Viral Hepatit Dergisi, 2021)
Objectives: Vertical transmission of hepatitis B virus, hepatitis C virus, (HBV, HCV) and human immunodeficiency viruses (HIV) infections is an important public health problem. The aim of this study was to determine the rates of hepatitis B, anti-HCV and anti- HIV seropositivities in pregnant women in a city and to evaluate the infections in terms of perinatal outcomes. Materials and Methods: In this retrospective study, 8,464 patients who gave birth in obstetrics and gynecology clinic were recorded. Seropositivity rates of pregnant women were investigated according to the results of hepatitis B surface antigen (HBsAg), HCV antibody and anti-HIV antibody. The rates were determined according to years and perinatal results and statistical comparison was made. Results: HBsAg seropositivity in pregnant women included in the study was 2.8 % (n=55) in 2015, 2.2% (n=52) in 2016, 2.3% (n=47) in 2017 and 2.2% (n=49) in 2018. The 4 year average was found to be 2.3% (n=203). There was no significant difference between the years (p>0.05). Among all our patients, 4-year mean anti-HCV seropositivity was 0.57% (n=49) and there was no difference between years (p>0.05). Anti-HIV seropositivity was found to be 0.09% on average, and there was no statistically significant difference over the years (p>0.05). Conclusion: Since hepatitis B, which is a preventable viral disease, has a risk of transmission during delivery and if it is transmitted to the fetus, it may lead to fatal complications at later ages, it is necessary to screen all pregnant women in terms of HBsAg seropositivity and to include it in an antepartum planning program to protect and treat newborns from infection. Although the transmission rate of HCV is low in the society, considering its clinical course, screening of HCV together with HIV in risky groups and pregnant women antibody positivity is considered important for the health of the society and newborns.